The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s12192-014-0545-0
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic elongation factor 2 kinase confers tolerance to stress conditions in cancer cells

Abstract: Eukaryotic elongation factor 2 (eEF2) is a member of the GTP-binding translation elongation factor family that is essential for protein synthesis. eEF2 kinase (eEF2K) is a structurally and functionally unique protein kinase in the calmodulin-mediated signaling pathway. eEF2K phosphorylates eEF2, thereby inhibiting eEF2 function under stressful conditions. eEF2K regulates numerous processes, such as protein synthesis, cell cycle progression, and induction of autophagy and apoptosis in cancer cells. This review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…4C). Eukaryotic elongation factor-2 kinase (eEF2K) has been reported to contribute to carcinogenesis [15][16]. Intriguingly, western blot analysis showed that the protein expression of eEF2K in the GAPLINC silencing group decreased significantly compared with the control group (Fig.…”
Section: Lncrna Gaplinc Silencing Inhibits the Tumor Growth Of Nsclc mentioning
confidence: 92%
“…4C). Eukaryotic elongation factor-2 kinase (eEF2K) has been reported to contribute to carcinogenesis [15][16]. Intriguingly, western blot analysis showed that the protein expression of eEF2K in the GAPLINC silencing group decreased significantly compared with the control group (Fig.…”
Section: Lncrna Gaplinc Silencing Inhibits the Tumor Growth Of Nsclc mentioning
confidence: 92%
“…eEF2K-induced phosphorylation of eEF2 changes it into an inactive state, which, in turn, inhibits the protein translation. Expression and activation of eEF2K increase in tumor tissues from the pancreas and breasts, where eEF2K facilitates the proliferation and viability of tumor cells through positively modulating the cell cycle and autophagy (30). Thus, it has been proposed that eEF2K affects the pathogenesis of other cell proliferation-associated diseases than cancer.…”
mentioning
confidence: 99%
“…eEF2K is inactivated by phosphorylation at Ser359. eEF2K has been shown to also be upregulated in cancer (48,53,73,75). One study of particular interest looked at eEF2K in transformed cells under acute verses chronic nutrient deprivation (46).…”
Section: Discussionmentioning
confidence: 99%